TEOLOGI MUSIBAH : DISKURSUS MUSIBAH MELALUI PENDEKATAN QUR’ANI - Husni, Muhammad; Hasani Z, Jufri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the factors causing a disaster so that it can provide an answer to the hypothesis that disasters are natural phenomena or punishments from God. This research is a literature study using a theological or Qur'anic approach in understanding a disaster or calamity. This research uses the thematic interpretation method, namely by collecting verses of the Qur'an related to disasters or calamities and analyze the causal factors behind the disaster. The results of this study reveal that the occurrence of disasters, including disasters that are considered pure disasters basically it cannot be separated from human attitudes and actions that are negligent (human error) and do not heed divine rules both in relation to God and to nature (other than God). This disaster can function as azab and iqab (punishment and torment) as a result of human actions or as a trial and temptation (test and trial) against faith even though one cannot identify and ascertain the position of each calamity.Keywords : Disaster, Natural Phenomena, Punishments, and Qur'anic